Heterogeneity in Response to Treatment of Adolescents with Severe Obesity: The Need for Precision Obesity Medicine - Ryder, Justin R. (Obesity (Silver Spring), 2019)
OBJECTIVE: Treating pediatric severe obesity is challenging due to the complex biological, behavioral, and environmental factors that underpin the disease. The multifactorial etiology of obesity combined with the physiologic complexity of the energy regulatory system contributes to treatment variability. The goal of this secondary analysis of pooled data was to describe the degree of individual variation in response to various interventions among adolescents with severe obesity. METHODS: Data from 3 centers across the United States conducting either lifestyle (n=53), pharmacotherapy (n=40), or metabolic and bariatric surgery (MBS; n=78) interventions were pooled. Inclusion criteria were severe obesity at baseline and at least one follow-up visit >30 days after treatment start. RESULTS: Change in BMI following intervention ranged from −50.2% to +12.9%, with each intervention (lifestyle [range: −25.4% to 5.0%], pharmacotherapy [range: −10.8% to 12.9%], MBS [range: −50.2% to −13.3%]) exhibiting wide individual variation in response. Changes in cardiometabolic risk factors demonstrated similarly high variability. CONCLUSIONS: Adolescents with severe obesity demonstrated a high degree of heterogeneity in terms of BMI reduction and cardiometabolic risk factor response across treatment modalities. Reporting individual response data in trials and identifying factors driving variability in response will be vital for advancing precision medicine approaches to address obesity.